Adaptation through diverse crop and livestock systems—The story of Edwin and Doreen, the adaptation pioneer farmers from Sotik, Kenya - Onyango, Polycarp Otieno; Kiptoo, Emmaculate (International Livestock Research Institute, 2025)
Edwin and Doreen are part of about 50 pioneer adaptation farmers that ILRI is working with in two counties to promote farmer-led local solutions to climate change in dairy. The specific aim is to increase milk yields for small holder farmers, ensure low age at first livestock calving, short calving intervals, and adaptation to climate change through improved feeding practices, diverse crop and livestock systems for multiple income streams. The pioneer adaptation farmers share locally developed solutions through farmer-led networks and peer-to-peer learning. Through this system, by the end of 2024, ILRI reached 15,000 households with knowledge about improved feeding practices and climate change adaptation.